To solve the system of equations using the substitution method, we start with the given equations:
- \( x - 2y = 3 \) (Equation 1)
- \( 4x - 8y = 12 \) (Equation 2)
We’ll first solve one of the equations for one variable and substitute it into the other equation. Let's solve Equation 1 for \( x \):
From Equation 1: \[ x = 2y + 3 \]
Next, we can substitute this expression for \( x \) into Equation 2:
\[ 4(2y + 3) - 8y = 12 \]
Now, let's simplify this equation:
\[ 8y + 12 - 8y = 12 \]
The \( 8y \) terms cancel out: \[ 12 = 12 \]
This statement is always true, indicating that the two equations are dependent. Thus, they represent the same line, which means there are infinite solutions.
So, the correct response is:
infinite solutions